Influences on the physical demands of International Womens Sevens Rugby - Reyneke, Jan Harm Thomas (Auckland University of Technology, 2016)
The use of time motion analysis and match analysis to gain a better insight into the demands of match play has been well documented across various sports. The information gathered from these techniques has enabled coaches and conditioning coaches to better prescribe trainings and conditioning to suit the specific demands of match play. The World Rugby (WR) Women’s Seven’s Series was only established in 2012. As a consequence, research specific to the demands of match play is sparse in the women’s game [1-6]. It was therefore the initial aim of this thesis to systematically review all the relevant literature pertaining to the physical demands of both men’s and women’s rugby sevens match play. The review highlighted some key findings in the male game that were unknown in the female game. Firstly, it was identified that there may be a difference in the match play demands between positional groups in the male game. Secondly, it would appear that a much larger gap in the physical demands of match play exists between international and domestic players in the female game when compared to the male game. Finally, the review highlighted the lack of literature pertaining to the influence of match significance and match outcomes on the physical demands of match play, specific to the female game. Following the review, Chapter 3 consisted of a longitudinal study exploring whether a difference exists in the physical demands of match play between positional groups and pool and cup games (play off). Fifteen members from a highly ranked international team (age, 24.3±3.87 years; body mass, 67.5 ± 6.31 kg; height, 168 ± 7.15 cm; mean ± SD) participated in this investigation. Global Positional System (GPS) running data, along with match play activities, were analysed to identify whether differences exist between these groups. The main findings from this study highlighted the lack of clear difference in the physical demands between positional groups. The second finding displayed an increase in the physical demands between pool and cup games. These increases however, where mainly through match activities and not the running demands. It was concluded that as the match importance increases, the demand on greater skill execution, rather than the running demands, becomes of greater significance. Following Chapter 3, another longitudinal study was conducted exploring whether the score differential in winning games influenced the physical demands of match play. The same team participated in this investigation. Winning score differentials were classified as either small (<21 points) or large (>21 points) and GPS running data along with match play activities were analysed to identify whether differences exist. Total distances covered were moderately greater in high score differential games (3.8, ±5.2 m/min; mean difference, ±99% confidence limits). Small differences (high-low) were also observed for distance covered at the following speeds: 2-3.5m.s-1 (1.3, ±3.4 m/min), 5-6m.s-1 (0.8, ±1.5 m/min) and ≥6m.s-1 (1.4, ±1.6 m/min). There were moderately greater numbers of missed tackles (0.2; mean count) and lineouts (0.5) in low score differential versus high score differential games. Coaches and conditioning coaches should consider the total running and match activity demands when matches are won by large or small margins. Specific recovery protocols should be considered for matches that have either higher running demands or higher match activity demands.
Keywords: Womens Sevens; Rugby